Influence of phosphorus fertilizer on melon (Cucumis melo L.) production - Mendoza-Cortez, Juan Waldir [UNESP]; Cecílio-Filho, Arthur Bernardes [UNESP]; Grangeiro, Leilson Costa; de Oliveira, Fábio Henrique Tavares (My University, 2014)
The Mossoró-Assu agricultural region is one of the most important melon-producing and -exporting regions in Brazil. The soils of this region, though, are characteristically poor in phosphorus (P), a most important nutrient for high productivity. Two melon (Cucumis melo L.) cultivars, Olimpic express and Iracema, were used to evaluate doses of P in a randomized complete block design with six treatments (0, 50, 100, 200, 300, and 400 kg ha-1 P2O5) and five replicates. The following characteristics were evaluated: foliar P content, total (TNF) and commercial (NFC) number of fruits per hectare, total (TP) and commercial (CP) productivities, P level in the soil (determined by two methods: anionic exchange resin (AER) and Mehlich-1), and the optimum economic dose (OED) of P. Foliar P, TNF, NFC, TP, CP, and both determinations of P levels in the soil were significantly affected by P doses for both cultivars. The maximum NFC (18 239 fruits ha-1) and the CP (28.98 t ha-1) for Olimpic express were achieved with 319.5 and 310.1 kg ha-1 P2O5, respectively. The maximum NFC (20 361 fruits ha-1) and CP (35.5 t ha-1) for Iracema were observed with 400 kg ha-1 P2O5. The OED for Olimpic express was 306.1 kg ha-1 P2O5. The OED was not calculated for Iracema, because the CP was adjusted to a linear equation. P levels in the soil, corresponding to the maximum CP, were 49.6 mg dm-3 (AER) and 44.5 mg dm-3 (Mehlich-1) for Olimpic express and 46.2 mg dm-3 (AER) and 51.4 mg dm-3 (Mehlich-1) for Iracema. Foliar P was 3.2 g kg-1 for Olimpic express and 3.2 g kg-1 for Iracema. Iracema, with a larger number of fruits and high commercial productivity, was the most efficient cultivar in unfertilized soil. Olimpic express responded better to phosphorous fertilization by increasing the number of fruits and its commercial production.
Keywords: Cucumis melo; Cultivars; Economic dose; Fertilization